ANALISIS MOTIF DAN HASIL KOMPETENSI PESERTA PELATIHAN KEJURUAN OTOMOTIF DI UPT BALAI LATIHAN KERJA KABUPATEN KULON PROGO: Indonesia, Inggris - Taufiq Miftahudin; Sutiman Sutiman (Department of Automotive Engineering Education, Faculty of Engineering, Yogyakarta State University, 2025)
Abstract The research aimed to determine the results of the Kulon Progo Regency UPT BLK training and the participants' motives for participating in automotive vocational training. Training improves the quality of human resources so that people can have abilities and skills. This research is quantitative and descriptive. The research subjects were alumni of automotive vocational training participants at UPT BLK Kulon Progo Regency, totaling 22 people in the TKR training and 10 in the TSM training. The data collection method uses documentation of training results, closed questionnaires, and semi-structured interviews, which expert judgment, namely automotive lecturers, has validated. The data obtained was analyzed using descriptive statistics. The training results showed that 100% of participants passed the training, and 88% passed the competency test. This shows that the training is going well, and training obstacles can be overcome well, and is supported by the level of satisfaction of the training participants, which is in the satisfied and very satisfied categories. However, alumni distribution needs to be improved, especially in providing information on job opportunities and handling participants' interest in working outside the region. The results of participants' motives for participating in training can be ranked as follows: 1) knowledge motive, 2) facility motive, 3) work preparation motive, 4) portfolio motive, and 5) motive to fill free time. Keywords: Balai Latihan Kerja (BLK), Satisfaction, Motive, Vocational School Alumni Abstrak Tujuan penelitian ini adalah untuk mengetahui hasil pelatihan UPT BLK Kabupaten Kulon Progo dan motif peserta mengikuti pelatihan pada kejuruan otomotif. Pelatihan merupakan peningkatan kualitas sumber daya manusia yang dimiliki, sehingga dapat menjadikan seseorang memiliki kemampuan dan keterampilan. Penelitian ini merupakan penelitian deskriptif kuantitatif. Subjek penelitian merupakan alumni peserta pelatihan kejuruan otomotif UPT BLK Kabupaten Kulon Progo yang berjumlah 22 orang pada pelatihan TKR dan 10 orang pada Pelatihan TSM. Metode pengumpulan data menggunakan dokumentasi hasil pelatihan, kuesioner tertutup dan wawancara semi terstruktur yang telah divalidasi oleh judgement ahli yaitu dosen otomotif. Data yang diperoleh dianalisis dengan statistik deskriptif. Hasil pelatihan menunjukkan 100% peserta lulus pelatihan dan 88% peserta lulus uji kompetensi. Hal ini menunjukkan bahwa pelatihan berjalan dengan baik dan kendala pelatihan dapat diatasi dengan baik dan didukung dengan tingkat kepuasan peserta pelatihan yang berada pada kategori puas dan sangat puas. Namun, penyaluran alumni perlu adanya peningkatan, khususnya dalam penyediaan informasi peluang kerja dan penanganan minat peserta untuk bekerja diluar daerah. Hasil motif peserta mengikuti pelatihan dapat diurutkan sebagai berikut: 1) motif ilmu 2) motif fasilitas 3) motif persiapan kerja 4) motif portofolio 5) motif mengisi waktu luang. Kata kunci: Alumni SMK, Balai Latihan Kerja (BLK), Kepuasan, Motif